Formação docente em ensino diferenciado responsivo à diversidade de todos os alunos - Milhomem, Walkyria de Araújo (2023)
The SARS-CoV-19 pandemic experienced in Brazil between 2020 and 2021 has highlighted the weaknesses of the Brazilian education system in terms of learning gaps. In this context, the Research Group on Human Resources Training for Special Education GP-FOREESP developed a research project called "Collaborative Action to Mitigate Educational Inequalities Resulting from the COVID-19 Pandemic: Contributions from Research on School Inclusion - (PAC-COVID19)". The present study is one of the five modules of the project which aimed to develop, implement and evaluate a continuing education program based on Differentiated Education (DE). The participants were 38 professionals: 01 manager, 09 resource room teachers, 10 pedagogical coordinators, 10 from the multidisciplinary team and 08 elementary school teachers (1st to 3rd grade). The study was conducted through three virtual meetings lasting 2 hours/class, held fortnightly online, with synchronous activities such as availability of readings, videos and activities available on the Google Classroom platform, as well as collaborative actions to draw up lesson plans. Data was collected through oral interviews, teachers' reports of filming training meetings, the researcher's field diary and the final training evaluation form. The data was analyzed using the ATLAS.ti software and the results obtained are presented in two sections denominated as DE principles and Program Training Assessment. These discuss the results in terms of the participants' understanding of the theoretical concepts and principles presented and how they were articulated in their practical activities. As a result of the training, the participants developed classes with proposals that took into account the different levels of readiness, interests and learning profiles, revealed through the choice of content, processes and products developed in flexible groupings. The students' engagement in the classes taught by the docents, as well as their knowledge of the new teaching methods, resulted in 65.15% of participants giving the highest marks for their satisfaction with the training program. Thus, we conclude that the provision of continuing education in DE had an impact on improving the engagement and protagonism of the students in the initial grades in which the teachers participating in the training taught, as well as contributing to increasing the effectiveness of teaching due to the various skills that were developed in a single lesson and significantly improving lesson planning, also managing to contribute to the process of continuous assessment of the public of Special Education without the need for individualized adaptations. The training had an innovative theoretical/practical proposal that contributed to teaching in heterogeneous classrooms insofar as it made it possible to respond to the diversity of the students. Thus, this approach proved to be efficient in favoring inclusive schools, and the success of its applicability can also be associated with collaboration between educators and working conditions that guarantee better time for joint lesson planning.